2015
DOI: 10.12659/ajcr.894022
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Fulminant Pneumonia Caused by Methicillin-Sensitive Staphylococcus aureus Negative for Major High-Virulence Factors Following Influenza B Virus Infection

Abstract: Patient: Male, 32Final Diagnosis: MSSA pneumoniaSymptoms: Cough • dyspnea • feverMedication: Meropenem • levofloxacin • vancomycin • peramivirClinical Procedure: Diagnosed based on CT images • sputum culture • PCRSpecialty: Infectious DiseasesObjective:Rare diseaseBackground:Increasing evidence has indicated that Staphylococcus aureus pneumonia complicated with influenza virus infection is often fatal. In these cases, disease severity is typically determined by susceptibility to antimicrobial agents and the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Co-infection with the influenza B virus and bacterial pneumonia has been reported worldwide (3,4). But to our knowledge, this is the first report of fatal fulminant pneumonia and septicemia in China in which co-incident infection with both influenza B and PVL-positive MSSA was laboratory confirmed.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Co-infection with the influenza B virus and bacterial pneumonia has been reported worldwide (3,4). But to our knowledge, this is the first report of fatal fulminant pneumonia and septicemia in China in which co-incident infection with both influenza B and PVL-positive MSSA was laboratory confirmed.…”
Section: Discussionmentioning
confidence: 74%
“…But to our knowledge, this is the first report of fatal fulminant pneumonia and septicemia in China in which co-incident infection with both influenza B and PVL-positive MSSA was laboratory confirmed. Several reports indicated that influenza virus infection results in epithelial cell injury and facilitates the occurrence of secondary bacterial infection through multiple mechanisms of immunological injury (3,(6)(7)(8)(9). The hypothesis of immunological injury caused by the influenza virus B in the host includes decreased bacterial phagocytosis among alveolar macrophages, downregulated expression of toll-like receptors, and functional inhibition of neutrophil recruitment by type I interferon initiated by the viral infection (10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations